A Survey of Indonesian Science Teachers' Experience and Perceptions toward Socio-Scientific Issues-Based Science Education - Safwatun Nida; Sri Rahayu; Ingo Eilks (MDPI AG, 2020)
This survey explored Indonesian science teachers’ experience and perceptions toward science teaching that is based on socio-scientific issues (SSIs). The participants were asked whether or not they already used corresponding practices in their own teaching and whether they experienced any challenges in implementing SSI-based pedagogies. Further focal points were the teachers’ views on student competencies that can be fostered through SSI-based education, the connection of SSI-based pedagogies with students’ character formation, potential topics for implementing SSIs in science education, and the teachers’ interest in such implementation. Data were collected with the help of a questionnaire that was administered to 99 science teachers. This was then followed up by interviews with 20 intentionally selected teachers taken from the overall sample. The study revealed that teachers’ familiarity with SSI-based pedagogies varies greatly. Regardless of their familiarity with the term, some of the teachers had already implemented corresponding practices at varying levels of intensity. Although almost all of the participants saw potential in SSI-based pedagogies for increasing student competency development and character formation, most of the respondents did not implement SSI-based teaching very often in their lessons. They mentioned several challenges that hindered them in implementing SSI in their teaching practices. Reasons included the lack of necessary students’ competencies, a lack of teacher expertise, the content in the official curriculum, inadequate facilities, and a lack of time for lesson preparation and implementation. When asked for ideas in implementing SSI-based education, teachers basically suggested topics related to the environment or technology as suitable for SSI-based education. In spite of the many challenges, most of the teachers were still interested in implementing SSIs in their classes.